ENDOPHYTIC BACTERIA: OPTIMIZATON OF ISOLATION PROCEDURE FROM VARIOUS MEDICINAL PLANTS AND THEIR PRELIMINARY CHARACTERIZATION - Anjum, Nawed; Chandra, Ramesh (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Objective: The aim of this study was to the isolate the endophytic bacteria, optimize its isolation procedure and preliminary characterization of isolated endophytes. Methods: Ethanol, Sodium hypochlorite, and Mercuric chloride at various concentration and duration were employed to optimize the surface sterilization for the isolation of endophytes from Catharnatus roseus, Ocimum sanctum Mentha arvensis and Stevia rebaudina. Microscopic and biochemical characterization of isolates was carried out such as Gram reaction, Endospore staining, Motility, Catalase and Oxidase activity. Results: A total of 35 endophytic bacteria have been isolated from four medicinal plants. Combination of 2% sodium hypochlorite, 70% ethanol and 0.1%, mercuric chloride was found effective for the surface sterilization of Catharnatus roseus and Ocimum sanctum. In case of Mentha arvensis and Stevia rebaudina, 70% ethanol, 2 % sodium hypochlorite was found suitable for the surface sterilization of. In preliminary screening 18 isolates were gram positive cocci, 11 were gram negative bacilli, 6 were found to be gram positive bacilli,18 isolates showed positive results for endospore staining, 24 gave positive results for catalase test and 13 gave positive results for oxidase test and 15 isolates were found to be motile. Conclusion: Ethanol, Sodium hypochlorite and mercuric chloride were found effective decontaminating agents at optimum condition. In preliminary screening diverse colony, different shapes, color, margins and textures were observed. Most of the isolates were found Gram positive.